Surface meteorological, ceilometer and radiosonde measurements near the Salton Sea on 2020-02-22 - Amato T Evan (PANGAEA, 2022)
Contained here are meteorological measurements made during a dust storm in southern California on February 22, 2020. The measurements were made from a research site located at 33.169 N and -115.856 E and managed by the lab of Professor Amato Evan (Scripps Institution of Oceanography and University of California San Diego. The data collection includes a netcdf file of backscatter measurements made from a Vaisala CL51 ceilometer and generated via output from BLView, a netcdf file containing 1-minute averaged surface meteorological measurements made from a Vantage Pro2 Davis Met Station, and separate datasets containing measurements made from 4 radiosondes launched throughout the coarse of this day. All data are described in detail and analyzed in: Measurements of a Dusty Density Current in the Western Sonoran Desert by A. T. Evan, W. Porter, R. Clemensha, A. Kuwano, and R. Frouin, J. Geophys. Res. Atmos., 2022, doi:10.1029/2021JD035830.